Papillary Neoplasms of the Salivary Duct System: A Review - Agaimy, Abbas (Surgical Pathology Clinics, 2020)
Papillary lesions of the salivary duct systems are uncommon. They encompass a heterogeneous group of benign, intermediate, and potentially aggressive neoplasms. With a few exceptions, historical descriptive terms such as papillary adenocarcinoma, papillary cystadenocarcinoma, and papillary adenoma are being replaced by defined entities, at same time acknowledging the papillary features as a histologic pattern. The evolving genetic landscape of these lesions increasingly permits their reproducible categorization. This article discusses those papillary proliferations encountered in the salivary glands with a focus on intraductal papillary mucinous neoplasms and cystadenomas. Intraductal carcinomas and sialadenoma papilliferum are addressed in separate articles in this issue.
CRIS-Team Scopus Importer:2020-12-25
Keywords: AKT1 mutations; Cystadenoma; Intraductal papillary mucinous neoplasm; Intraductal papilloma; IPMN; Mucinous; Papillary; Salivary glands